PENGARUH PENGGUNAAN MEDIA GAMBAR SERI TERHADAP KETERAMPILAN MENULIS KARANGAN NARASI SISWA KELAS IV SD NEGERI 37 PEKANBARU - Putri, Ulva Ratna; Kurniaman, Otang; Alpusari, Mahmud (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This study aims to determine the effect of the using pictures series toward writing ability on narrative text of fourth grade students of SDN 37 Pekanbaru. The subjects of this study were students of class IVA which amounted to 31 people. The methd used in this research is experimental method with one-group pretest-posttest design research design. The method used in this study was conducted in one class without comparison group. Instruments used as data in research is essay test in the form of writing assignment narrative.Hypothesis testing is done by using t test. The result show that the students ability in writing narrative essay before using the picture series include in the category of less skilled with the average value of 65,3. While after the using pictures series include in the skilled category with an average value of 83,4. Then based on testing the hypothesis that Ha is accepted if the lower is negative and upper value is possitive or significant value (2tailed) > α. From test result pretest and posttest lower value is negative and upper value is negative or sig. (2tailed) = 0,000 < α=0,05 Ho rejected and Ha accepted. Where Ha in this study is there are differences in narrative writing skills on the pretest and posttest class IVA SD Negeri 37 Pekanbaru, then there is the effect of using the pictures series toward writing ability on narrative text of fourth gradestudents of SD Negeri 37 Pekanbaru.Keywords: Media pictures series, writing ability, narrative text